Vaginal Cuff Dehiscence with Evisceration - A Rare Complication after Total Abdominal Hysterectomy - Akter, Sumaya; Akhter, Sayeba (Bangladesh Journal of Obstetrics & Gynaecology, 2025)
Background: Vaginal cuff dehiscence (VCD) is an uncommon complication occurring after hysterectomy. The incidence of vaginal cuff dehiscence depends on the operation rectovaginal, abdominal, or laparoscopic approach. Among them incidence is higher following laparoscopy compared to total abdominal hysterectomy and vaginal hysterectomy. The cause of this striking difference is unknown. Factors which are probably contributing to the occurrence of VCD include opening and closure techniques of the vaginal cuff (VC), suture materials used, age, body mass index (BMI), use of medication possibly influencing the healing process, smoking, and menopausal status. Sexual intercourse seems to be the triggering event in most cases. However, it is unclear which patients are at risk for developing this serious complication Method: We present the case of a woman aged 52 year, menopausal who underwent total abdominal hysterectomy for twisted ovarian cyst. Vault was closed with delayed absorbable suture. 3 months after surgery, the patient developed symptoms including per vaginal bleeding, lower abdominal pain and difficulty in micturition shortly after intercourse and were diagnosed as vaginal cuff dehiscence with evisceration. Result: Patient undergoing surgical treatment may experience poor wound healing of the vaginal cuff. Resuming sexual activities before proper healing of the wound has triggered vaginal cuff dehiscence. Conclusion: Optimisation of co-morbidities and improvement of general condition preoperatively, meticulous closure of vaginal cuff and proper antibiotic coverage post-operatively remain key factor in the prevention of vaginal cuff dehiscence. Avoidance of early resumption of sexual intercourse is also a important predisposing factor. Bangladesh J Obstet Gynaecol, 2024; Vol. 39(1): 44-48